Persepsi Mahasiswa Terhadap Penerapan Blended Learning Dalam Pengajaran Akuntansi Pemerintahan: Tingkat Kepuasan dan Rancangan Pengajaran - Dewi Pebriyani; Vita Fitria Sari; Ade Elsa Betavia (Wahana Riset Akuntansi, 2021)
One of the trends in today's learning methods is to combine face-to-face meetings with online lectures. The application of blended learning for technical subjects such as accounting is still limited. This study aims to determine students' perceptions of the application of blended learning in government accounting teaching, the level of student satisfaction with the government accounting teaching process using traditional methods compared to blended learning, as well as the correct composition in the application of blended learning between face-to-face lectures and online teaching via e-learning in government accounting teaching. Respondents in this study were students who had passed government accounting courses. Data analysis was performed using the Mann Whitney difference test. The results of this study indicate that there are differences in student perceptions of the application of traditional learning and blended learning as many as 5 statement items. The results of this study also conclude that learning design using the blended learning method can be implemented for teaching government accounting but this does not mean eliminating face-to-face meetings, lecturers must design a combination of online and face-to-face meetings that are considered ideal by taking into account the number of students in the class and the number of students in the class. members in study groups Keywords: Blended learning; Course design; Government accounting; Learning method; Students’ satisfaction.